Morphological and Molecular Investigation of Non-Simulium damnosum Black Flies in Cameroon Using Nuclear ITS 2 and Mitochondrial Cox 1 Genes - Pierre Kamtsap; Archile Paguem; Flore Nguemaïm Ngoufo; Alfons Renz (Insects)
Background: This study enhances knowledge of black fly biodiversity in Cameroon by integrating morphological and molecular analyses. A total of 19 Simulium species were identified from 1184 pupae collected across 13 sites, using morphological examination of gills and DNA sequencing of Cox1 and ITS2 markers. Key findings include the first report of 2 not yet described (based on identification keys used) species in Cameroon and confirmation of S. vorax and S. dentulosum as known vectors of onchocerciasis. DNA sequences have been deposited in GenBank for reference. Methods: Combining morphological and molecular approaches revealed more species diversity than previously described, showing the potential of molecular techniques in black fly study. Notably, the presence of species not typically associated with human-biting behavior (e.g., S. cervicornutum) raises the possibility that such flies could act as vectors under favorable conditions. Conclusion: This study underscores the importance of identifying Simulium species for understanding their role in pathogen transmission. The results provide a foundation for further research on undescribed Simulium species and their potential vectorial capacities. Future studies should explore the ecological and behavioral factors influencing vector status, especially in the context of environmental changes. By bridging morphology and DNA analysis, this research advances the study of black flies and sets the stage for improved vector monitoring and disease control in Cameroon and beyond.